Synergistic wound healing effects of Hibiscus rosa-sinensis and Centella asiatica extracts combination (HRSCA): in vivo and 3D organotypic models - Zulkurnain, Izyan Hazirah; Sayuti, Mumtaz; Kamaruzaman, Allisya Sofea; Maniam, Sandra; Halim, Hasseri; Xian, Law Jia; Ali, Aida Azlina (Prince of Songkla University, 2025)
Objective: Hibiscus rosa-sinensis and Centella asiatica are medicinal plants used as an alternative therapy for wound healing, and many studies have reported evidence of their effectiveness in treating wounds. This study aimed to evaluate the histological and molecular changes observed in the healing properties of a Hibiscus rosa-sinensis and Centella asiatica extracts combination (HRSCA) on wounds. Material and Methods: Twenty-four rats were randomly divided into 4 groups (untreated, 10% Povidone-Iodine solution; 5.0% and 10.0% HRSCA). The excisional wounds were inflicted using a tissue biopsy punch and treated once daily for 14 days. The wound healing properties and tensile strength test were measured. A 3D organotypic skin model using human keratinocytes and human dermal fibroblast cell lines in a collagen type 1 scaffold was developed to further evaluate the wound healing properties. Full-thickness wound was induced and was either treated with 5% HRSCA or left untreated. qRT-PCR was used to evaluate the affected genes involved in the wound healing pathway. Results: The in vivo model showed no significant differences in tensile strength between groups. However, HRSCA treatment significantly enhanced wound healing. The 3D assay revealed HRSCA modulated genes like COL53A, CSF2, CXCL11, CXCL5, IL6ST, ITGA5, PLAT, and WISP1. Conclusion: HRSCA enhanced wound closure in in vivo and 3D organotypic skin models, potentially through several pathways, such as inflammatory as well as extracellular matrix and adhesion pathways. The findings from this study provide substantial evidence regarding the wound healing potential of HRSCA.